1992
DOI: 10.1002/mar.4220090105
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of compulsiveness in the consumer‐marketplace domain

Abstract: The marketing literature exhibits a consistent lack of concern to recognize the distinct differences among the various possible manifestations of compulsiveness in the consumer‐marketplace domain. The practice of using terms pertaining to different manifestations of compulsiveness synonymously, especially when the meaning of the term “compulsive behavior” is itself under debate, creates further semantic uncertainties that hinder typological endeavors in the budding area of abnormal or deviant consumer behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…As such, demographic variables, such as gender, are consistent with the gender-role hypothesis. Third, with respect to the consequences of self-expressiveness in shopping, past research has focused on the dark side of shopping, such as compulsive shopping (e.g., Hosch and Loewenstein, 1991;Hirschman, 1992;Kwak et al, 2003;Mowen and Spears, 1999;Nataraajan and Goff, 1992;O'Guinn and Faber, 1989;Rindfleisch et al, 1997;Roberts et al, 2003;Roberts and Tanner, 2005). Future research may test the hypothesis that compulsive shopping moderates the relationship between perceived shopping contribution to life satisfaction and subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…As such, demographic variables, such as gender, are consistent with the gender-role hypothesis. Third, with respect to the consequences of self-expressiveness in shopping, past research has focused on the dark side of shopping, such as compulsive shopping (e.g., Hosch and Loewenstein, 1991;Hirschman, 1992;Kwak et al, 2003;Mowen and Spears, 1999;Nataraajan and Goff, 1992;O'Guinn and Faber, 1989;Rindfleisch et al, 1997;Roberts et al, 2003;Roberts and Tanner, 2005). Future research may test the hypothesis that compulsive shopping moderates the relationship between perceived shopping contribution to life satisfaction and subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Nataraajan and Goff (1992) indicated that terms such as spending, buying, and shopping have been used interchangeably; yet, as they indicate, distinctions between these various forms of aberrant consumer behavior exist.…”
Section: Compulsiw Buying Behaviormentioning
confidence: 97%
“…However, it is well known that rigorous and highly organized processing may characterize only part of consumer behavior in the marketplace. In reality, consumers are also found to be impulsive (Beatty & Ferrell, 1998;Cobb & Hoyer, 1986;Dholakia, 2000;Rook & Fisher, 1995), distractible (AriasBolzmann, Chakraborty, & Mowen, 2000;Lord & Burnkrant, 1993), reliant on incomplete and/or irrelevant information (Johnson & Levin, 1985;Kivetz & Simonson, 2000;Meyvis & Janiszewski, 2002;Ross & Creyer, 1992), and in some cases, addicted to compulsive shopping (Nataraajan & Goff, 1992;O'Guinn & Faber, 1989). Impulses may be moderated by cognitive evaluation (Dholakia, 2000), unless self-control failure enables unplanned, spontaneous purchases to occur (Baumeister, 2002).…”
Section: Introductionmentioning
confidence: 99%